Regulation of appetite and growth of Atlantic salmon (Salmo salar L.) and effect of water oxygen, temperature and dietary energy - Vikeså, Vibeke (Aquaculture, 2017)
High water temperature combined with low dissolved oxygen (LO or hypoxia) is one of the most challenging environmental conditions farmed fish experience. The oxygen requirement of fish increases in parallel to this, which limits the aerobic energy metabolism and consequently reduces feed intake and growth of fish. The global ocean warming followed by reduced oxygen availability, is expected to exacerbate associated physiological stress on fish in several areas where Atlantic salmon are currently farmed. Understanding the impact of temperature and limited oxygen on growth regulatory mechanisms and the energy metabolism, will be of significant relevance to both cultured and wild fish populations. Conditions of high temperature and hypoxia are related with reduced feed intake and growth in fish. It is unclear whether the low oxygen availability directly affects growth regulatory mechanisms, and if low feed intake is the primary cause of depressed growth under LO conditions. Studies of appetite and growth regulation in salmon under such conditions are few, and considerations of the fluctuating character of endocrine signals and nutrient absorption are scarce. Limitation of the aerobic energy metabolism under reduced oxygen availability is further restricted by a thermal increase. It is therefore interesting to find out how high energy diets can potentially impact appetite and growth regulation under LO conditions. This thesis therefore investigated mechanisms by which LO and high temperature conditions impact appetite and growth regulation in seawater adapted Atlantic salmon. Free amino acid (FAA) and endocrine dynamics in relation to meal time were also studied. Four fish trials were conducted, including the following variables; dissolved oxygen (DO; LO and high, HO), temperature and digestible energy (low and high, LE and HE). Endocrine appetite and growth signalling was investigated through analyses of plasma ghrelin and IGF-1 concentration, and mRNA levels of the growth hormone receptor (ghr1) and insulin like ...